The Central Scotia Sea Floor – Palaeo-Oceanic Plate, Young Riftogenous Plate or Palaeo-Land Scotia? - Schenke, H.W.; Udintsev, G.B. (Український антарктичний журнал, 2009)
Although the bathymetry and geophysics of the Scotia Sea basin is rather well studied in general and is discussed in many publications there are still remaining questions about tectonics of its Central Part. In the western part of the Sea tectonic nature is well demonstrated by West rifted ridge and in the eastern part by East back-arc rift. The floor of the central part does not show such well expressed tectonic features. The usual interpretation of that part of basin floor is described as introduced fragment of the Pacific paleo-Plate or as newly created oceanic plate resulted by supposed rifting. Recent bathymetry and other geophysics survey is complemented with geological sampling lead to hypothesis on the existence there of a large relict of continental bridge between South America and West Antarctica.